2015
DOI: 10.1242/dev.122176
|View full text |Cite
|
Sign up to set email alerts
|

Meis1 coordinates a network of genes implicated in eye development and microphthalmia

Abstract: Microphthalmos is a rare congenital anomaly characterized by reduced eye size and visual deficits of variable degree. Sporadic and hereditary microphthalmos have been associated with heterozygous mutations in genes fundamental for eye development. Yet, many cases are idiopathic or await the identification of molecular causes. Here we show that haploinsufficiency of Meis1, which encodes a transcription factor with evolutionarily conserved expression in the embryonic trunk, brain and sensory organs, including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 80 publications
7
42
1
Order By: Relevance
“…This data together with the fact that only simultaneous deletion of Meis1 and Meis2 in PLE leads to an arrest of lens development in pre-placodal stage strongly suggests that both Meis1 and Meis2 are expressed and essential for early eye development. Nevertheless, it is very likely that Meis1 and Meis2 fulfill the redundant function only in specific developmental stages and processes (our data and [46]), while having many discrete functions in the embryo even within the eye development.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This data together with the fact that only simultaneous deletion of Meis1 and Meis2 in PLE leads to an arrest of lens development in pre-placodal stage strongly suggests that both Meis1 and Meis2 are expressed and essential for early eye development. Nevertheless, it is very likely that Meis1 and Meis2 fulfill the redundant function only in specific developmental stages and processes (our data and [46]), while having many discrete functions in the embryo even within the eye development.…”
Section: Discussionmentioning
confidence: 87%
“…However, it is likely that Meis1 and Meis2 regulate other factors contributing to early lens development such as the ones identified for Meis1 [46]. It was recently shown that Meis1 regulates either directly or indirectly the expression of genes involved in patterning, proliferation and differentiation of the neural retina, and that haploinsufficiency of Meis1 causes micropthalmic traits and visual impairment in adult mice [46]. Based on the fact that Marcos et al could not detect Meis2 expression at early stages of eye development, authors considered only Meis1 function to be critical for early mouse eye development [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In plants, BEL1-like proteins function in a tandem complex with KNOX-type TFs to regulate numerous aspects of growth and development (Chen et al, 2003;Smith and Hake, 2003;Brambilla et al, 2007;Rutjens et al, 2009;Khan et al, 2012). Related genes from the TALE class in animals also control important processes of growth and differentiation (Machon et al, 2015;Marcos et al, 2015;Merabet and Galliot, 2015;Villaescusa et al, 2016). The physical interaction between KNOX and BEL1 proteins and its functional significance have been documented in numerous plant species (Bellaoui et al, 2001;Müller et al, 2001;Smith et al, 2002;Chen et al, 2003Chen et al, , 2004.…”
Section: Stbel5 a Mobile Signal Controlling Development In Potatomentioning
confidence: 99%
“…MEIS1 also plays a critical role in development and stem cells regulation [46]. Various genetic alterations occur in AML that lead to overexpression of the MEIS/HOXA9 complex, which plays a synergistic causative role in acute myeloid leukemia (AML) development [7–10].…”
Section: Introductionmentioning
confidence: 99%